A tripartição das funções no Estado e as Súmulas Vinculantes: análise histórica e impactos na atualidade brasileira - Kumasaca, Daniel Mascarin Pires (2015)
The Brazilian legal system allows many interpretations of its model, its institutions and its scope in society. Among the institutes, the summary bindings introduced by EC 45/2004 make possible to do analysis of the entire political, social and Brazilian legal system, since they arise from abnormalities that may jeopardize state security. The idea is to promote, through philosophical discussion and the historical reconstruction of social and political ideals, how summary bindings affect the current landspace of the Federative Republic of Brazil. It is not just about addressing the issue related to judicial activism resulting from summary bindings, but also and mainly explores the institute, confronts concepts and puts down theories, grounded in the study of philosophical models treated along the dissertation. Therefore, we intend to address not only the positions against the summary bindings, as well as to refute the favorable understandings, which exist by evidence and are found in the majority doctrine of constitutional law Brazilian. We work in order to focus not only on legal institutions, but we try to find at the heart of the society itself, manners and the discussion about the scope of power and its way of working in the state. Conceiving the story, along with the philosophical study were outstanding to achieve the results listed here, from the theoretical foundation to the critical development of the institutes, existing institutions and concepts in Brazil and it is precisely the tripartite model of separation of executive functions, legislative and judiciary that the major part of this work is framed, especially when we analyze the judicial activism of the Supreme Court and the prerogative created with summary bindings, since it is the last resort of the Brazilian system, reason why the analysis about the State General Theory stands as crucial to the final understanding of the work